2019
DOI: 10.1103/physrevx.9.031036
|View full text |Cite
|
Sign up to set email alerts
|

Giant Magnetic Quantum Oscillations in the Thermal Conductivity of TaAs: Indications of Chiral Zero Sound

Abstract: Charge transport of topological semimetals has been in the focus of intensive investigations because of their non-trivial band topology. Heat transport of these materials, on the other hand, is largely unexplored and remains elusive. Here we report on an observation of unprecedented, giant magnetic quantum oscillations of thermal conductivity in the prototypical Weyl semimetal TaAs. The oscillations are antiphase with the quantum oscillating electronic density of states of a Weyl pocket, and their amplitudes a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Early theoretical studies of the electronic contribution to the thermal conductivity in Weyl semimetal without considering the CZS modes obtain the B 2 dependence for the thermal conductivity under magnetic field [53], which is quite different from the contribution from the CZS introduced above. Such a field-dependent violation of the Wiedemann-Frantz law has already been seen in the thermal conductivity measurement of TaAs under a magnetic field, indicating the possible contribution from the CZS [54]. We note that for realistic systems which are not deeply in the chiral limit, the CZS will also acquire nonzero velocity along the transverse direction of the magnetic field as well, which is caused by the accompanying normal current during the oscillation.…”
Section: Thermal Properties Of Chiral Zero Soundsupporting
confidence: 70%
“…Early theoretical studies of the electronic contribution to the thermal conductivity in Weyl semimetal without considering the CZS modes obtain the B 2 dependence for the thermal conductivity under magnetic field [53], which is quite different from the contribution from the CZS introduced above. Such a field-dependent violation of the Wiedemann-Frantz law has already been seen in the thermal conductivity measurement of TaAs under a magnetic field, indicating the possible contribution from the CZS [54]. We note that for realistic systems which are not deeply in the chiral limit, the CZS will also acquire nonzero velocity along the transverse direction of the magnetic field as well, which is caused by the accompanying normal current during the oscillation.…”
Section: Thermal Properties Of Chiral Zero Soundsupporting
confidence: 70%
“…An alternative signature of the chiral anomaly was found in the thermoelectric properties in Cd 3 As 2 studied by Jia et al [5], showing that this approach bears more promise. Very recently, a new heat-transport mechanism called chiral zero sound has been predicted in Weyl semimetals [11] and could be used to explain the observed giant thermal conductivity in Weyl semimetal TaAs [12] and anomalous heat current in GdPtBi [13]. Here, we report our systematic study of the thermoelectric properties (both Seebeck and Nernst effects) of layered Hafnium pentatelluride (HfTe 5 ) single crystals and show that the observed results are consistent with a nontrivial electronic structure.…”
Section: Introductionmentioning
confidence: 53%
“…Numerous theoretical and experimental studies have revealed that the chiral fermions can host rich fascinating physical phenomena, such as the chiral zero sound [39,40], colossal chiral ultrafast photocurrents [41], and photoinduced anomalous Hall effects [42]. Our discovery introduces a new degree of freedom to study the chiral fermions, which would facilitate uncovering more exotic behaviour associated with the chiral fermions in materials.…”
Section: Discussionmentioning
confidence: 87%